Interobserver agreement on the sonographic severity grading of shoulder impingement syndrome - Raham Bacha; Syed Amir Gilani; Asif Hanif; Iqra Manzoor (The Ultrasound Journal, 2022)
Abstract Background Shoulder impingement syndrome is the painful entrapment of the soft tissues between the acromion and the humeral head. The severity of shoulder impingement could be graded according to the limitation of shoulder joint moment. The reliability of sonographic findings in the grading of shoulder impingement severity grading is required to be evaluated by the consistency of findings between the observers. Purpose To assess the interobserver agreement in the sonographic severity grading of shoulder impingement syndrome with the help of a ratio between acromion-to-greater tuberosity distance in the abduction and neutral arm position. Material and methods Patients were examined by two independent observers in the coronal approach with neutral arm position. Acromion-to-greater tuberosity distance was measured in abduction and neutral shoulder position. The ratios of the distances in the abduction and neutral position were calculated to grade the severity of shoulder impingement syndrome. Results A total of 78 shoulders were included in this study. A strong agreement was found for the grading of shoulder impingement severity grading between the two independent observers with Kappa value of 0.94. And correlation between the results of the two observers for the severity grading of shoulder impingement syndrome was significant at 0.01 level. Conclusion Severity grading of the shoulder impingement syndrome was performed based on the ratio of acromion-to-greater tuberosity distance in abduction and neutral arm position. However, the sonographic findings were consistent and a strong interobserver agreement was seen in this sonographic severity grading.